STRUKTUR GEOLOGI PADA ZONA TRANSISI ANTARA BUSUR VOLKANIK BUKIT BARISAN DENGAN CEKUNGAN BELAKANG BUSUR : CONTOH DI DAERAH SUMATRA UTARA - -, Iyan Haryanto (Bulletin of Scientific Contribution, 2011)
Structural pattern in Sumatra controlled by oblique subduction between Eurasian Plate with Indo-Australian Plate, resulting the structure dominated by strike-slip dextral faults. According to the position of subduction, the strike slip fault generally trending northwest-southeast.The older faults that already formed in the basement rocks (pre-rift) reactivated become normal faults under the influence of transtensional (syn-rift). This tectonic process then produce some tertiary sedimentary basin in the adjacent area. Furthermore, in the Late Tertiary it is reactivated again under the influence of transpressional (post-rift). This later tectonic event cause all sedimentary rock strongly folded and faulted, followed by magmatism/volcanism activity. This whole tectonic activity produced the Barisan Mountain Range.The transpressional process created high and low area, which could make the basement rock uplifted and separate the distribution of tertiary sedimentary in the different locations.